NetProfiler: Profiling Wide-Area Networks Using Peer Cooperation - Padmanabhan, Venkat; Ramabhadran, S.; Padhye, Jitu (Fourth International Workshop on Peer-to-Peer Systems (IPTPS), 2005)
Our work is motivated by two observations about the state of networks today. Operators have little visibility into the end users’ network experience while end users have little information or recourse when they encounter problems. We propose a system called NetProfiler, in which end hosts share network performance information with other hosts over a peer-to-peer network. The aggregated information from multiple hosts allows NetProfiler to profile the wide-area network, i.e., monitor end-to-end performance, and detect and diagnose problems from the perspective of end hosts. We define a set of attribute hierarchies associated with end hosts and their network connectivity. Information on the network performance and failures experienced by end hosts is then aggregated along these hierarchies, to identify patterns (e.g., shared attributes) that might be indicative of the source of the problem. In some cases, such sharing of information can also enable end hosts to resolve problems by themselves. The results from a 4-week-long Internet experiment indicate the promise of this approach.